The feasibility and acceptability of a novel anxiety in bipolar disorder intervention compared to treatment as usual: A randomized controlled trial. Issue 10 (19th July 2018) - Jones, Steven H.; Knowles, Dawn; Tyler, Elizabeth; Holland, Fiona; Peters, Sarah; Lobban, Fiona; Langshaw, Brian; Hilton, Claire; Long, Rita; Gantt, Kay; Owen, Rebecca; Roberts, Chris; et al.
Abstract : Background: Comorbid anxiety is common in bipolar disorder (BD) and associated with worse clinical outcomes including increased suicidality. Despite effective psychological treatments for anxiety, research into treating anxiety in BD is underdeveloped. This paper describes a novel psychological intervention to addressa nxietyi n context ofb ipolard isorder (AIBD). Methods: Adults with BD and clinically significant anxiety symptoms were randomized to AIBD plus treatment as usual (TAU) or TAU alone. AIBD offered 10 sessions of psychological therapy using a formulation‐based approach. Feasibility and acceptability were evaluated through recruitment, retention, therapy attendance, alliance, fidelity, and qualitative feedback. Clinical outcomes were assessed at baseline, 16, 48, and 80 weeks: interim assessments of relapse at 32 and 64 weeks. Results: Seventy‐two participants were recruited with 88% retention to 16 weeks and 74% to 80 weeks (similar between arms). Therapy participants attended x ¯ 7.7 ( SD 2.8) sessions. Therapeutic alliance and therapy fidelity were acceptable. Qualitative interviews indicated that participants valued integrated support for anxiety with BD and coping strategies. Some suggested a longer intervention period. Clinical outcomes were not significantly different between arms up to 80 weeks follow‐up. Conclusions: AIBD is feasible and acceptable but lack of impact on clinical outcomes indicates that adaptations are required. These are discussed in relation to qualitative feedback and recent literature published since the trial completed.